HOMOGENIZATION AND CRYSTALLIZATION TO IMPROVE TECHNOLOGICAL PROPERTIES OF WHOLE MILK POWDER FOR APPLICATIONS IN FOOD INDUSTRY - Valéria M. Santos; Júlia d’A. Francisquini; Tatiana S. Lima; Natalia C. Mesa; Luiz Fernando C. de Oliveira; Rodrigo Stephani; Antônio F. de Carvalho; Ítalo T. Perrone (Química Nova)
The aim of this study was to evaluate the influence of different pressures of homogenization on whole milk powder with crystallized lactose on free fat content and particle size. Three homogenization pressure levels were applied. The powder produced at homogenization pressure of 75/5 MPa presented a smaller number of particles in the region < 1 μm (39.28%) and higher free fat content (13.78%) when compared to the powder produced at conventional homogenization pressure (15/5 MPa), which presented 59.40% particles in the region < 1 μm and 5.03% of free fat. Milk powder produced at 0/0 MPa presented the lowest number of particles in the region < 1 μm (24.60%) and the highest free fat content (19.39%). This study showed that the powder produced at a homogenization pressure of 15/5 MPa, which is commonly used in the industry, produces a crystallized milk powder with less suitable properties than the one obtained without homogenization.